Conventionality Control of Domestic Law - Yota, Negishi (Beiträge zum ausländischen öffentlichen Recht und Völkerrecht, 2022)
Through gaining lessons from the doctrine of constitutionality control, the book deals principally with conventionality control achieved by judicial adjudicators. This monograph fills the gap in comparative international human rights law by analysing the practice of conventionality control in Europe and Latin America. Based on the empirical data, the author normatively envisions a 'trapezium' model of conventionality control with the features of openness, substantivism and human-centrism, which overcomes the limits of the closed, formalist, and State-centric 'pyramid' model. Author: Yota Negishi, Associate Professor of Public International Law, Seinan Gakuin University, Fukuoka, Japan.